Case Report: Venoarterial Extracorporeal Membrane Oxygenation Support for Caowu-Induced Cardiac Arrest - Ren, Binbin; Wang, Liming; Chen, Kun; Chen, Lin; Wang, Huabin (Frontiers in Medicine, 2021)
Abstract Introduction Caowu, the main root of the Aconitum plant, is widely used in China. Aconitine is the main toxic component of Aconitum, which can cause a variety of malignant arrhythmias and lead to death. Four patients who developed malignant arrhythmia after drinking medicinal wine containing Caowu were reported in this study. Cardiac arrest occurred soon after symptom onset. All patients received venoarterial extracorporeal membrane oxygenation (VA-ECMO) support after conservative medical treatment had failed. Patients who were directly transferred to our hospital received VA-ECMO support earlier than patients who were first treated at a local hospital. One patient received hemoperfusion in the emergency room before VA-ECMO support; the other three patients began hemoperfusion after VA-ECMO treatment. Surviving patients who received VA-ECMO earlier after symptom onset showed no obvious neurological complications. The patient who received a longer cardiopulmonary resuscitation time but received hemoperfusion before VA-ECMO had mild neurological complications. The mortality rate was 25% (1 of 4 patients). Two patients had thrombotic complications in venous vessels. Conclusions Cardiogenic shock due to refractory ventricular tachycardia caused by aconitine is lethal. Conservative supportive treatment did not provide a short-term antiarrhythmic effect and the cardiogenic shock was not well controlled. VA-ECMO treatment combined with hemoperfusion is promising temporary support to successfully treat aconitine-induced cardiogenic shock caused by refractory ventricular tachycardia.